Analysis of the Compliance of the Vaccination Schedule against Pneumococcal Infection in Young Children - I. V. Feldblium; A. V. Bikmieva; Yu. A. Zakharova; S. S. Eresko; E. N. Melnik (Эпидемиология и вакцинопрофилактика, 2018)
Background. Vaccination is considered by the world community as the main measure of the fight against pneumococcal infection [1–3]. Immunization of children has been carried out since the end of 2014.  Goals. To study the compliance of the vaccination scheme against pneumococcal infection in young children and its influence on vaccination efficacy.Methodology. Evaluation of the compliance of the vaccination schedule against pneumococcal infection and the impact on morbidity in young children was carried out under the conditions of epidemiological observational descriptive and analytical («cohort») researches. Expert assessment is made of medical records of 52 patients, and 200 electronic medical cards and 200 cards of prophylactic vaccination in children were born in of 2015 and 2016.Results. The high importance of adherence to the vaccination scheme against pneumococcal infection was established not only in the prevention of disease and also in reducing carriage of S. pneumoniae. The greatest effect of pneumococcal immunization was observed in children who received the first vaccination before the age of 6 months and with a completed course of vaccination.Conclusion. Timeliness of immunization of young children against pneumococcal infection is a significant factor in ensuring preventive efficacy of immunization.